Development of a decision model for the selection of exoskeletons for application in automotive production plants - Woun Yoong Gan; Raja Ariffin Raja Ghazilla; Hwa Jen Yap; Suman Selvarajoo; Zhang Jieshu (PLoS ONE, 2025)
This paper presents the development of a decision model for the selection of exoskeletons for application in automotive production plants. The decision model consisted of three stages: (1) Human Factor-Failure Mode and Effect Analysis (HF-FMEA), (2) augmentation analysis, and (3) Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). This decision model is called the Decision Model for Exoskeleton Selection in the Automotive Industry (DMESAI). An industrial case study was conducted with 13 experts from the automotive industry to test and verify the usability of the DMESAI. The findings suggest that the DMESAI is feasible to determine the need for exoskeletons in automotive production processes, narrowing the suitable types of exoskeletons for specific tasks, and addressing user’s preferences.